Corrosion resistant materials handbook - De Renzo, D. J.; Mellan, Ibert (Noyes Data Corp., 1985)
Provides ways for the concerned engineer or manager to cut losses due to corrosion by choosing suitable commercially available corrosion resistant materials for a particular application. The Handbook is also useful to equipment designers and others as a screening guide in choosing materials for equipment with specific corrosion resistance requirements.
Revised edition of: Mellon, Ibert. Corrosion resistant materials handbook. 3rd ed. 1976.
Includes indexes.
Keywords: Corrosion resistant materials -- Handbooks, manuals, etc.; elektronické knihy; electronic books